Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00011-009-0097-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase 1 and cyclooxygenase-2 enzymes are targets of muscarinic activation in normal and inflamed NIH3T3 cells

Abstract: Activation of muscarinic acetylcholine receptors can mimic mild inflammatory conditions or can deepen pre-existing inflammation, establishing a fine-tuned set-up on fibroblasts that in turn could be alerting the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Both IL-1β and the cell-associated form IL-1α stimulate elongation. In other tissues, fibroblasts are thought to be intermediaries in the immune reaction during an inflammatory progression that includes chemokine signaling via prostaglandins and nitric oxide release [41]. We show that this phenomenon of cilia elongation, in response to the inflammatory cytokine IL-1, is not just active in chondrocytes but is also present in fibroblasts and therefore may have implications for all inflamed tissues.…”
Section: Discussionmentioning
confidence: 74%
“…Both IL-1β and the cell-associated form IL-1α stimulate elongation. In other tissues, fibroblasts are thought to be intermediaries in the immune reaction during an inflammatory progression that includes chemokine signaling via prostaglandins and nitric oxide release [41]. We show that this phenomenon of cilia elongation, in response to the inflammatory cytokine IL-1, is not just active in chondrocytes but is also present in fibroblasts and therefore may have implications for all inflamed tissues.…”
Section: Discussionmentioning
confidence: 74%
“…It is well known that different inflammatory stimuli can activate the NF‐κB signalling pathway and that this activation can lead to an increase in the expression of several proteins (Bonizzi and Karin, ). Although we demonstrated that NF‐κB is constitutively active in NIH3T3 cells (Español et al ., ), our results indicate that this transcription factor is not involved in the de novo expression of M 3 and M 5 receptors in these cells.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we showed for the first time that muscarinic acetylcholine receptor protein expression is induced under inflammatory conditions. In addition, we demonstrated that this effect is time‐dependent, because short‐term stimulation with the same concentrations of LPS and IFN‐γ failed to induce the expression of M 3 and M 5 receptors (Español et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, we have not established the expression of thromboxane synthase that generates TXA2, several studies have established that NIH3T3 cells express all the necessary components for activating the TPαR. This includes arachidonic acid [44] and COX-1/2 [45], [46] that are responsible for generating prostaglandin H2 (that in itself can work as an agonist on the TP receptor) [47], [48]. 2) Co-expression of AT1R with a mutant TPαR R130V, deficient in G protein coupling, enhanced the potency of AngII signaling to a much lesser degree than did the wild-type TPαR (Fig.…”
Section: Discussionmentioning
confidence: 93%